Incidence of short-term complications and associated factors after primary trabeculectomy in Chiang Mai University Hospital - Leeungurasatien, Thidarat (Indian J Ophthalmol, 2016)
BACKGROUND: To determine the incidence of early postoperative complications and associated factors after primary trabeculectomy in Thai glaucoma patients. DESIGN: This was a retrospective observational study performed in Chiang Mai University Hospital. PARTICIPANTS: One hundred and eighteen glaucoma patients participated in the study. METHODS: All glaucoma patients underwent primary trabeculectomy with mitomycin C (MMC) using fornix-based conjunctival flap technique between December 2011 and May 2013. Surgical complications during the first 3 months of follow-up were recorded, and associated risk factors were analyzed. MAIN OUTCOME MEASURES: The incidence of posttrabeculectomy complications was the main outcome measure. RESULTS: One hundred and eighteen eyes of 118 patients were included. Early postoperative complications developed in 55 eyes (56.7%). Complications included hypotony (25 eyes, 27.2%), serous choroidal detachment (CD) (14 eyes, 15.6%), subconjunctival hemorrhage (12 eyes, 13.0%), hyphema (11 eyes, 12.4%), bleb leak (8 eyes, 8.8%), encapsulated bleb (2 eyes, 2.2%), aqueous misdirection (1 eyes, 1.1%), corneal epithelial defect (1 eyes, 1.1%), and overfiltration (1 eyes, 1.1%). There were no reported cases of endophthalmitis or blebitis. Hypotony was associated with serous CD (P = 0.006), and hyphema was associated with neovascular glaucoma (NVG) patients (P = 0.009). NVG was not associated with the increased rate of surgical failure (P = 0.083). CONCLUSIONS: The incidence of early complications after first-time trabeculectomy with MMC was high (56.7%) in this Thai clinic setting, but most were transient and self-limited conditions. The correlations between hypotony and CD as well as hyphema and NVG were compatible with the previous studies.